2000
DOI: 10.1055/s-2000-6232
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Synthesis of Aliphatic and Aromatic N-Sulfonyl Aldimines

Abstract: N-Arenesulfonyl aldimines were prepared from aliphatic and aromatic aldehydes in a two-step transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 8 publications
1
124
1
2
Order By: Relevance
“…To a solution of imine 3a [14] (0.1 mmol, 26.0 mg) and catalyst 1 [6] (0.02 mmol, 6.2 mg) in THF (1.0 mL) was added malonic acid half thioester 2a [15] (0.2 mmol, 39.2 mg). The reaction mixture was stirred at the temperature and the time stated, without any precaution of excluding moisture or air, after which 4a was obtained through purification of the reaction mixture by chromatography on silica gel (EtOAc/n-hexane, 1:8) as a white solid; yield: 33.0 mg (83 %); mp 117 8C; …”
Section: Experimental Section (S)-s-phenyl 3-phenyl-3-(tosylamino)promentioning
confidence: 99%
“…To a solution of imine 3a [14] (0.1 mmol, 26.0 mg) and catalyst 1 [6] (0.02 mmol, 6.2 mg) in THF (1.0 mL) was added malonic acid half thioester 2a [15] (0.2 mmol, 39.2 mg). The reaction mixture was stirred at the temperature and the time stated, without any precaution of excluding moisture or air, after which 4a was obtained through purification of the reaction mixture by chromatography on silica gel (EtOAc/n-hexane, 1:8) as a white solid; yield: 33.0 mg (83 %); mp 117 8C; …”
Section: Experimental Section (S)-s-phenyl 3-phenyl-3-(tosylamino)promentioning
confidence: 99%
“…This chemistry was applied unsuccessfully toward the synthesis of enolizable N-sulfonyl aldimines and unfortunately this method shares a common limitation with several other methods of N-tosylaldimine synthesis 18,33,34,36,37 in that it does not appear to be applicable to the synthesis of N-sulfonyl aldimines derived from aldol condensations being obtained instead. We have also studied the reaction of sulfonamide with ketones.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] Various practical and simple synthesis of N-tosyl imines are known. [18][19][20][21][22][23][24][25][26] The toluenesulfonyl activating group of imine can be removed easily by treatment with Mg/MeOH, 27,28 treatment with phenol in refluxing HBr/HOAc solution with addition of H 2 O, 29 or treatment with SmI 2 in THF at room temperature. 30 Our group found that the Ln(O i Pr) 3 was a very effective catalyst for the aza-Henry reaction when the N-tosyl imine was used as the substrate (cat., 5 mol %; yield, 99%).…”
Section: Introductionmentioning
confidence: 99%